A STUDY ON THE EFFECT OF MARINE GROWTH ON FIXED JACKET PLATFORM DAMAGED BY CORROSION - ABDUL LATIF, MOHD FATEHAH (Universiti Teknologi PETRONAS, 2017)
There are much more concerns nowadays on the reliability and integrity asset management of oil and gas sector since that this industry is always being viewed as an ever-changing large scale development under complex environment. In Malaysian water where jacket structure is highly adopted as the offshore platforms and these structures had been found out that more than half of the numbers are operating beyond its design life. In addition to the extra loading and aging effects on the jacket members, one of the biggest obstacles being faced by offshore operator is corrosion and marine growth.